KATA TANYA DALAM KONSTRUKSI INTEROGATIF BAHASA MANDAILING - Rodiyah Harahap; Mulyadi Mulyadi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study discusses the polar interrogative construction in Mandailing. This study aims to analyze the form of interrogative in Mandailing. The research data is a mandailing sentence that comes from related literature on interrogative. This research employs questions words which of the thoughts of foreign and Indonesian linguists. The research method used is descriptive method which employs substitution, permutation, and reference techniques. The result of this research shows that: Question words as interrogative markers can indicate different interrogative contruction types.Key words: question words, interrogative construction, rhetoric interrogative